Disruption of mitochondria-associated ER membranes impairs insulin sensitivity and thermogenic function of adipocytes - Wang, Chih-Hao; Wang, Chen-Hung; Hung, Pen-Jung; Wei, Yau-Huei (Frontiers in Cell and Developmental Biology, 2022)
The prevalence and healthcare burden of obesity and its related metabolic disorders such as type 2 diabetes (T2D) are increasing rapidly. A better understanding of the pathogenesis of these diseases helps to find the therapeutic strategies. Mitochondria and endoplasmic reticulum (ER) are two important organelles involved in the maintenance of intracellular Ca2+ and ROS homeostasis. Their functional defects are thought to participate in the pathogenesis of insulin resistance or T2D. The proper structure and function of the mitochondria-associated ER membranes (MAMs) is required for efficient communication between the ER and mitochondria and defects in MAMs have been shown to play a role in metabolic syndrome and other diseases. However, the detailed mechanism to link MAMs dysfunction and pathogenesis of insulin resistance or T2D remains unclear. In the present study, we demonstrated that the proteins involved in MAMs structure are upregulated and the formation of MAMs is increased during adipogenic differentiation of 3T3-L1 preadipocytes. Disruption of MAMs by knocking down GRP75, which is responsible for connecting ER and mitochondria, led to the impairment of differentiation and ROS accumulation in 3T3-L1 preadipocytes. Most importantly, the differentiated 3T3-L1 adipocytes with GRP75 knockdown displayed inactivation of insulin signaling pathway upon insulin stimulation. Moreover, GRP75 knockdown impaired thermogenesis and glucose utilization in brown adipocytes, the adipocytes with abundant mitochondria that regulate whole-body energy homeostasis. Taken together, our findings suggest that MAMs formation is essential for promoting mitochondrial function and maintaining a proper redox status to enable the differentiation of preadipocytes and normal functioning such as insulin signaling and thermogenesis in mature adipocytes.